Kompetensi Profesional Guru MA An-Nur Setupatok Kabupaten Cirebon - Agus Prayitno (Eduvis : Jurnal Manajemen Pendidikan Islam, 2020)
Professional competence is the ability to master broad and in-depth learning material that enables guiding students to meet the competency standards set out in National Education Standards. A professional teacher is not only competent in the mastery of the material, the use of appropriate methods, but there is also a desire to always improve the professional abilities and the desire to always develop strategies in carrying out their duties as instructors as well as educators so that the teaching-learning process can reach the level optimal. The results of the study are based on data obtained from observations, interviews and documentation, the professional competence of teachers in MA Annur Setupatok Cirebon District shows 1). The teacher has an academic qualification according to the subject he teaches is almost high at 83.3%, 2). The teacher chooses learning material that is taught according to the level creatively, 3). The teacher develops professionalism on an ongoing basis by taking reflective actions, 4). The teacher uses information and communication technology to develop themselves. Abstrak Kompetensi Profesional merupakan kemampuan penguasaan materi pembelajaran secara luas dan mendalam yang memungkinkan membimbing peserta didik memenuhi standar kompetensi yang ditetapkan dalam Standar Nasional Pendidikan. Seorang guru profesional tidak hanya berkompeten dalam penguasaan materi, penggunaan metode yang tepat, akan tetapi juga ada keinginan untuk selalu meningkatkan kemampuan profesional tersebut dan keinginan untuk selalu mengembangkan strategi-strategi dalam melaksanakan tugasnya sebagai pengajar sekaligus pendidik agar proses belajar-mengajar dapat mencapai tingkat yang optimal. Hasil penelitian berdasarkan data yang diperoleh dari observasi, wawancara dan dokumentasi, kompetensi professional guru di MA Annur Setupatok Kabupaten Cirebon menunjukkan 1). Guru memiliki kualifikasi akademik sesuai mata pelajaran yang diampunya hampir tinggi sebesar 83,3 %, 2). Guru memilih materi pembelajaran yang diampu sesuai dengan tingkatan secara kreatif, 3). Guru mengembangkan keprofesionalan secara berkelanjutan dengan melakukan tindakan reflektif, 4). Guru memanfaatkan teknologi informasi dan komunikasi untuk mengembangkan diri.